PENGARUH IMPLEMENTASI HOLDING & SUBHOLDING TERHADAP KINERJA KARYAWAN DAN PENCAPAIAN KINERJA BISNIS : STUDI KASUS PADA PT KPI - Ery Gunarto; Lamtiur H. Tampubolon; Heru Prasadja (Jurnal Riset Multidisiplin Edukasi, 2025)
The impact of Holding and Subholding Implementation is expected to provide significant improvement in employee performance as well as optimization of profits and operations as well as cost efficiency for PT KPI. The company's performance becomes faster, more agile, and concise in the decision-making process. This study uses a quantitative research method with primary data sources through a questionnaire with a five-point Likert scale. The respondents in this study were 84 employees at PT KPI in all KPI offices and Refinery Units (RU) of PT KPI, with a sampling technique of simple random sampling (SRS). The data analysis technique uses Spearman correlation analysis to test the strength of the relationship between two variables. The relationship between the Holding and Subholding Implementation variables with employee performance has a correlation of 0.704 and the relationship between the Holding and Subholding Implementation variables with employee performance achievement is 0.798. These figures indicate that the Holding and Subholding Implementation variables have a strong influence on employee performance variables and their performance achievements. In the non-parametric analysis of the Kruskal-Wallis test, the results showed that there were significant differences between groups of variables in the holding and subholding implementation at PT KPI on employee performance and its achievements. This is indicated by the p-value in the Kruskal Wallis test of 0.00, which indicates a significant influence on the implementation of holding and subholding at PT KPI on employee performance and achievements. The results of a simple linear test show that every increase in one unit of value for the Implementation of the structure (holding and subholding) will increase 0.767 units of the value of employee performance achievement at PT.KPI employees with free implementation of the structure has a contribution effect of 67.3% on the employee performance achievement variable.